Gastric cancer patients less than 50 years of age exhibit significant downregulation of E-cadherin and CDX2 compared to older reference populations - Schildberg, Claus Wilhelm; Abba, Mohammed; Merkel, Susanne; Agaimy, Abbas; Dimmler, Arno; Schlabrakowski, Anne; Croner, Roland; Leupold, Joerg Hendrik; Hohenberger, Werner; Allgayer, Heike (Advances in Medical Sciences, 2014)
There is an increasing need to identify molecular markers, which can be used to prognosticate patient populations in gastric cancer. Whereas a significant number have been identified, very few have been characterized in the context of their ability to discriminate between young and old age groups in which a survival difference clearly exists.In this study, using immunohistochemistry, we evaluated three markers with proven involvement in gastric cancer. The p53 tumor suppressor, the cell adhesion glycoprotein epithelial cadherin (CDH1) and the caudal-related homeobox transcription factor (CDX2) all of these have important roles in the aetiopathogenesis and/or progression of gastric cancer.After adjustments for TNM stage, tumor grade, histopathological characteristics (Lauren classification), we found significant differences in the expression of these proteins, particularly E-cadherin and CDX2 between young and elderly patients. However, these differences did not amount to a significant difference in survival.This study demonstrates that the protein expression of p53, CDH1 and CDX2 significantly discriminates young patients with gastric cancer who have a better prognostic outlook from older patients, but this difference in expression does not contribute to a survival benefit.
EVALuna2:6583